Implementasi Edukasi Keuangan Untuk Menumbuhkan Kegemaran Menabung Pada Siswa Kelas IV SD Negeri 121313 Tanjung Pinggir, Pematang Siantar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe in depth the implementation of financial education in fostering a habit of saving among fourth-grade students at SD Negeri 121313 Tanjung Pinggir, Pematang Siantar. This activity is part of the Community Service Program (KKN) conducted by students of the State Islamic University of North Sumatra (UINSU). This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation of learning activities and the implementation of the savings program at school. The data obtained was then analyzed using the Miles and Huberman model, which includes the process of data reduction, data presentation, and interactive conclusion drawing. The results showed that the implementation of financial education by UINSU KKN students had a positive impact on changes in students' financial behavior. This financial education activity not only fostered financial skills but also shaped students' characters to be more responsible, disciplined, thrifty, and socially empathetic by encouraging them to share some of their savings. Thus, it can be concluded that the implementation of simple habit-based financial education through UINSU KKN activities has proven effective in fostering interest and enthusiasm for saving among elementary school students and contributes to shaping positive character traits that will be useful in their future lives.